THE INNOVATIONS EFFECTS AT COMPANY’S LABOUR PRODUCTIVITY - Nosova, Olga; Nosova, Tetiana (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The paper deals with the analysis of innovations effects on labour productivity, work quality, work contracts. Innovations are the basic factors in the growth of labour productivity. The innovations growth provides the release of labor force in low-tech sectors of the economy, the redistribution of workers in favor of high -tech sectors of the economy with high value added, and a major source of improving the welfare of the population and development of society. The methodology includes the interdisciplinary approach application based on institutional analysis, human resource management and comparative economics methods. The systematization of the basic approaches including systemic innovation system, the permanent organizations, innovation diffusion concept and etc. expand the object of study, and allows finding new directions in the study of the interdependence between innovations and labour productivity. The study of Ukrainian economic performance indicators of public R&D expenditures, innovation expenditures, employment in medium to high-tech manufacturing and high-tech services confirms decrease in public spending. The recent studies emphasize the main transformation in the world of work in terms of the labour market, social dialogue, and conditions of work, wages and incomes, and effects on the middle class. The strong institutions play significant role in the process of knowledge accumulation, creation well-functioning market system, institutional and infrastructure development. They are fully consistent with high employment and dynamic labour market functioning. The information technologies development contributes into the average annual growth of labour productivity in a range of the developed countries. The directions of preconditions for innovative development and the formation of partnerships and links between education, business, science, and innovation are proposed.